Laser-generated plasmas by graphene nanoplatelets embedded into polyethylene. (28th March 2017) - Torrisi, L.; Ceccio, G.; Restuccia, N.; Messina, E.; Gucciardi, P. G.; Cutroneo, M.
Abstract: Graphene micrometric particles have been embedded into polyethylene at different concentrations by using chemical–physical processes. The synthesized material was characterized in terms of mechanical and optical properties, and Raman spectroscopy. Obtained targets were irradiated by using a Nd:YAG laser at intensities of the order of 10 10 W/cm 2 to generate non-equilibrium plasma expanding in vacuum. The laser–matter interaction produces charge separation effects with consequent acceleration of protons and carbon ions. Plasma was characterized using time-of-flight measurements of the accelerated ions. Applications of the produced targets in order to generate carbon and proton ion beams from laser-generated plasma are presented and discussed.